Effects of fluoride intake on insulin sensitivity and insulin signal transduction - Chehoud, Keila Aziz [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Sumida, Doris Hissako [UNESP] (My University, 2008)
Forty seven-week-old male castrated Wistar rats were randomly divided evenly into a control group and a fluoride (F) group. The latter was given a single dose of NaF from a solution containing 1.0 mg F ion/kg bw, administered by gavage. After 30 min, the following experiments were performed: intravenous insulin tolerance test (0.75 U/kg bw) and determination of the insulin receptor substrate (pp 185-IRS-1/IRS/2) tyrosine phosphorylation status. The acute treatment with NaF promoted increased blood glycemia, but there were no significant changes in the insulin sensitivity and in the pp185 tyrosine phosphorylation status in the muscular or in the white adipose tissues. Copyright © 2008 The International Society for Fluoride Research Inc.
Keywords: Insulin receptor substrate; Insulin sensitivity; Insulin signal; Plasma fluoride; Rats and insulin